OpASHA : Improving Tuberculosis Treatment and Outcomes - Agapitova, Natalia (World Bank, Washington, DC, 2017)
Tuberculosis (TB) afflicts 2.8 million citizens in India, representing more than 30 percent of the world’s total burden. To control TB, complete adherence to treatment is crucial—under the World Health Organization’s (WHO) Directly Observed Therapy Short-course (DOTS) strategy. In this strategy, patients are required to take up to 75 doses under supervision over six months at a treatment center or in the presence of an observer. However, the scarcity or inaccessibility of treatment centers and truthful observers in hard to-reach areas often results in high default rates. Missing a dose or interrupting treatment is extremely dangerous, since those who default can relapse, or much worse, develop the deadlier, drug-resistant strain of TB. A continuing social stigma for those who have TB is also linked to incomplete treatment and lack of follow-up. There is poor data collection as well. Since 2006, Operation ASHA (OpASHA) has helped deliver the Last-mile connection to TB treatment and prevention in India by leveraging existing government infrastructure to supplement the country’s own efforts. OpASHA receives free medicines, diagnostic facilities and physician services from the national TB control program. Through a partnership with Microsoft Research, OpASHA has pioneered a biometric technology called eCompliance for treatment. OpASHA serves 10 million people in nine states across India, in addition to 2.2 million people in Cambodia. OpASHA has expanded to Cambodia, and its model has already been replicated in Uganda, Kenya, and the Dominican Republic.